Formulation of taste masked oro-dispersible tablets of ambroxol hydrochloride - Venkatesh, D P; Rao1, C G Geetha (Asian Journal of Pharmaceutics (AJP), 2014)
Ambroxol hydrochloride (HCL) is a potent mucolytic capable of inducing bronchial secretion. It is used in the treatment of asthma, bronchitis, and cough. But it is a very bitter drug and slightly soluble in water.Thus, in the work under taken, an attempt was made to mask the taste and to formulate into a oro-dispersible tablet by complexation with ion exchange resins, which also acts as super disintegrating agents. Since, these tablets can be swallowed in the form of dispersion, it is suitable dosage form for pediatric and geriatric patients. Cation exchange resins like Indion-204 and Indion-234 were utilized for the sorption of drug. Drug-resinates were prepared in drug to resin ratio of 1:5 and 1:6. The prepared tablets were evaluated for general appearance, content uniformity, hardness, friability, taste evaluation, mouth feel, wetting time, in vitro and in vivo disintegration time, and in vitro dissolution studies. Tablets with both the resins have shown quick disintegrating features, i.e., within 20 s, which is very characteristic of oro-dispersible tablets. Also, the dispersion not showing any bitter taste, indicate the capability of ion exchange resins used, both as taste masking and super disintegrating agents. Almost more than 90 percent of drug was released from both the formulations within 1 h. Further formulations were subjected to stability testing for 3 months at temperatures 25±5oC/60±5%RH and 40±5oC/75±5%RH. Both tablets have shown no appreciable changes with respect to taste, disintegration, and dissolution profiles.